Penerapan Sunnah Nabi Shallallahualaihi Wasallam., Ruqyah Syariyyah, di Klinik Surabaya Ruqyah Center - Adynata Adynata (An-Nida', 2013)
Ruqyah is one of the way of treatment of the disease, both physical and non-physical illness that existed before the advent of Islam. In the last ten years, ruqyah Syar’iyyah in Indonesia is growing rapidly with the implementation of a mass ruqyah by some Muslim groups. During its development, to meet the needs of the community will ruqyah, it is necessary to set up a clinic that specializes in serving the needs of the community and one of ruqyah experienced and intense clinics serving ruqyah until now is Ruqyah Surabaya Clinical Center which was founded in 2004. In the implementation of ruqyah, the ruqyah in Surabaya Ruqyah Center ruqyah can be made to either the human believers and disbelievers, and can also be carried out on a place like homes, shops, schools, dormitories, and others.